Care Work and Intra-Household Tensions during COVID-19 : Evidence from an Online Survey of Gig Workers in India - Abel, Martin; Tas, Emcet O.; Zahra, Najaf; D'Lima, Tanya; Kalashyan, Anna; Sethi, Jayati (World Bank, Washington, DC, 2020)
This note examines gender disparities in care work and intra-household tensions among online gig workers in India. The data was collected as part of an online experiment in April 2020, shortly after lockdown measures were implemented to mitigate the spread of the coronavirus disease (COVID-19). The findings show that childcare and eldercare responsibilities have increased for everyone during the lockdown, but women have disproportionately felt the burden of increased care work. Further, there was an increase in domestic violence, pointing to added stress and intra-household tensions. Policy makers need to incorporate a gender lens in emergency responses in order to promote women’s safety and wellbeing during COVID-19 and beyond.